2002
DOI: 10.1074/jbc.m111058200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of the Human Thromboxane Synthase Genein Vivo and in Vitro

Abstract: Thromboxane A 2 , a potent mediator of vasoconstriction and platelet aggregation, is synthesized from prostaglandin H 2 by thromboxane synthase (TXAS). We report here on promoter analyses of human TXAS using in vitro transcription and in vivo transfection methods. The 39-bp core promoter, containing both TATA and initiator elements, accurately initiates transcription in an orientation-dependent manner in a cell-free transcription system. Mutation of either TATA or initiator abolished transcriptional activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…20 Transcriptional targets of NF-E2 must serve essential roles in molecular mechanisms of platelet biogenesis and release. 5,36,49 Some pathways that seem to function downstream of NF-E2, such as prostaglandin metabolism 37,50 and inside-out integrin signaling, 38,39 are as yet not directly implicated in proplatelet formation or platelet release, although ␤1 tubulin is both down-regulated in NF-E2-null MKs 32 and required for optimal platelet production. 51 Here we identify Rab27b as a new component in NF-E2-dependent pathways of platelet assembly.…”
Section: Discussionmentioning
confidence: 99%
“…20 Transcriptional targets of NF-E2 must serve essential roles in molecular mechanisms of platelet biogenesis and release. 5,36,49 Some pathways that seem to function downstream of NF-E2, such as prostaglandin metabolism 37,50 and inside-out integrin signaling, 38,39 are as yet not directly implicated in proplatelet formation or platelet release, although ␤1 tubulin is both down-regulated in NF-E2-null MKs 32 and required for optimal platelet production. 51 Here we identify Rab27b as a new component in NF-E2-dependent pathways of platelet assembly.…”
Section: Discussionmentioning
confidence: 99%
“…To directly examine the effects of MafG transgenes on MARE-dependent transcription, we quantified mRNA encoding TXS, a well-characterized target gene of the p45-MafG heterodimer (36). The TXS expression levels correlated well with the PPF ratios, indicating that MafG represses MAREdependent transcription but that MafG K14R does not (Fig.…”
Section: Lysine 14 Is Necessary For Mafg To Repress Transcription In mentioning
confidence: 98%
“…Similarly, mafG-null mutant mice and, with increased severity, mafG Ϫ/Ϫ ::mafK ϩ/Ϫ compound mutant mice display defective proplatelet formation (PPF). Expression of the thromboxane synthetase (TXS) gene, a well-characterized megakaryocytic MARE-dependent target gene (36), was dramatically suppressed in megakaryocytes of p45-null mice (4), as well as in small maf mutant mice (20). Thus, a synergy between p45 and small Mafs was strongly implicated from these studies.…”
mentioning
confidence: 95%
“…[24][25][26][27] ChIP studies have demonstrated recruitment of p45 to the MAREs within the promoters of the p45 targets in a cell line with a megakaryocytic lineage. 28 Small maf mutant mice, as well as mafG and mafG::mafK compound mice also showed mild and severe thrombocytopenia, respectively, demonstrating that p45 and small Maf proteins function cooperatively in vivo. 29,30 On the other hand, we previously reported that BACH1 is expressed in megakaryocytes as well as in erythrocytes.…”
mentioning
confidence: 97%